INTERACTIVE COMPENSATORY MODEL: BASIS FOR THE DEVELOPMENT OF AN INTERACTIVE SUPPLEMENTARY READING MATERIAL FOR GRADE 7 LEARNERS - Elmawaddah Ersya; Bambang Widi Pratolo; Estrella T Arroyo (PROJECT (Professional Journal of English Education), 2024)
In the classroom, students had difficulties understanding the text's meaning and were unable to respond to questions. The reading process in this case was influenced by the teaching method and the lack of media. For a long time, the school's applied learning systems just gave the students access to materials and textbooks. Teachers need a learning model that will enable them to investigate the student's reading proficiency. In this particular case, the researcher tries to propose a solution by using the interactive compensatory model to propose interesting reading material. This model is the basis for creating reading learning instruments, specifically to improve reading comprehension. This model is the basis for creating reading learning instruments, specifically to improve reading comprehension. This research is development research. The type of data used in this study is a qualitative data. The data collection techniques and instruments used in this study are questionnaire and interviews. The result of this study is the eBook supplementary reading material for class 7 was rated as very good by English teacher and based on student responses and assessments.